Development of methodology for energy assessment of operational modes of work of power equipment - Овчаров, Сергей Владимирович; Стребков, Александр Андреевич (Technology audit and production reserves, 2015)
Development of scientific and technical proposals in the field of energy conservation, and increase the operational reliability of electrical power is continued in the article. One of the main indicators for assessing technical solutions is, as you know, the annual economic benefit of the development, expressed in national currency. However, due to the instability of the national currency, such estimate can’t be objective. It is considered that the weakest element of the design of power equipment is its electrical insulation. The main negative impact on its operating parameter is the temperature of heating, which in turn is a function of electric power losses in it. Evaluation of electric power losses in the power electrical equipment performed in units of electrical energy, and resource consumption of insulating structure – in units of insulation depreciation. As a result, it is difficult to assess the overall operational modes of electrical power equipment. Therefore, it is developed the technique of the energy assessment of operational modes of power equipment. In this paper we addressed the scientific and technical problem of estimating the economy of resources in the electrical power equipment by one indicator for which it is conducted research of the loss of electricity, together with the process of thermal deterioration of its isolation, and then their joint assessment. This task is performed by the example of induction motor with squirrel-cage rotor as the most widespread object of the power equipment.